Drought and Famine in India, 1870–2016. Issue 4 (15th February 2019) - Mishra, Vimal; Tiwari, Amar Deep; Aadhar, Saran; Shah, Reepal; Xiao, Mu; Pai, D. S.; Lettenmaier, Dennis
Abstract: Millions of people died due to famines in India in the nineteenth and twentieth centuries; however, the relationship of historical famines with drought is complicated and not well understood. Using station‐based observations and simulations, we reconstruct soil moisture (agricultural) drought in India for the period 1870–2016. We show that over this century and a half period, India experienced seven major drought periods (1876–1882, 1895–1900, 1908–1924, 1937–1945, 1982–1990, 1997–2004, and 2011–2015) based on severity‐area‐duration analysis of reconstructed soil moisture. Out of six major famines (1873–74, 1876, 1877, 1896–97, 1899, and 1943) that occurred during 1870–2016, five are linked to soil moisture drought, and one (1943) was not. The three most deadly droughts (1877, 1896, and 1899) were linked with the positive phase of El Niño–Southern Oscillation. Five major droughts were not linked with famine, and three of those five nonfamine droughts occurred after Indian independence in 1947. Plain Language Summary: India witnessed some of the most famous famines during the late nineteenth and early twentieth centuries. These famines caused millions of deaths primarily due to widespread crop failure. However, the role of agricultural drought in these famines remains unrecognized. Using station‐based observations and simulations from a hydrological model, we reconstructed agricultural droughts and established a linkage between famines and droughts over India. We find that a majority of famines were caused by large‐scale and severe soil moisture droughts that hampered the food production. However, one famine was completely due to the failure of policy during the British era. Expansion of irrigation, better public distribution system, rural employment, and transportation reduced the impact of drought on the lives of people after the independence. Key Points: Major drought events have been reconstructed in India during 1870–2016 India experienced seven major drought periods (1876–1882, 1895–1900, 1908–1924, 1937–1945, 1982–1990, 1997–2004, and 2011–2015) Out of six major famines that occurred during 1870–2016, five are linked to soil moisture drought, and one (1943) was not